The efficiency level of Indonesian banks in the Covid-19 pandemic era and its determinant - Ihsanul Ikhwan; Ririn Riani (Faculty of Economics, Universitas Islam Indonesia, 2022)
Purpose – This study aims to measure the efficiency level of Indonesian Banking in the period 2015-2020, especially in the year 2020 when the Covid-19 pandemic began to spread in Indonesia. In addition, the efficiency determinant was further analyzed to find some factors that affect banking efficiency.Methodology – Non-parametric approach-Data Envelopment Analysis (DEA) and Tobit Regression were employed as the research methods to determine determinants that affect efficiency level.Findings – The findings show that the efficiency level of Indonesian Banks experienced a decreasing trend in 2020. The impact of Covid-19 on banking efficiency was also confirmed by RTS, which was included in the Decreasing Return to Scale (DRS) category. Islamic banking scored a higher score of 0.66 than conventional banking, with a score of 0.59. In addition, Indonesian Banks' most crucial variable to be improved during the pandemic is total financing. This study also found that ROA and LDR/FDR significantly affects banking efficiency. Therefore, Indonesian Banks should maintain and increase their bank profitability and financing distributions to improve their efficiency.Implication – This research can be used as guidelines for policymakers, especially bank management, to improve their weaknesses in terms of banking efficiency. Originality – This study was the first research that focuses on measuring the efficiency of Islamic banks compared to conventional banks in Indonesia during the Covid-19 and precisely measures the bank's internal factors affecting bank efficiency.